1984
DOI: 10.1007/bf00252265
|View full text |Cite
|
Sign up to set email alerts
|

Changes in food intake during menstrual cycles and pregnancy of normal and diabetic rhesus monkeys

Abstract: Food intake of control and streptozotocin-diabetic rhesus monkeys was measured during menstrual cycles and pregnancy. Intake of control monkeys was lower at the time of ovulation than during other phases of the menstrual cycle. Intake of control monkeys was also low during most of pregnancy, but this was accompanied by normal fetal growth and net maternal weight gain. Diabetic monkeys ate more than controls in all conditions and their intake did not vary reliably according to reproductive status. It is suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Experimental studies of non-human primates could help address this possibility, although relatively few studies have been conducted. Initial data suggest that food intake is higher during the luteal than the follicular or ovulatory phase of the menstrual cycle in female monkeys (Bielert and Busse, 1983; Czaja, 1975, 1978; Kemnitz et al, 1984; Kemnitz et al, 1989; Rosenblatt et al, 1980). However, progesterone treatment alone has only inconsistently affected food intake in ovariectomized monkeys (Czaja, 1978; Roth et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies of non-human primates could help address this possibility, although relatively few studies have been conducted. Initial data suggest that food intake is higher during the luteal than the follicular or ovulatory phase of the menstrual cycle in female monkeys (Bielert and Busse, 1983; Czaja, 1975, 1978; Kemnitz et al, 1984; Kemnitz et al, 1989; Rosenblatt et al, 1980). However, progesterone treatment alone has only inconsistently affected food intake in ovariectomized monkeys (Czaja, 1978; Roth et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Dalvit, 1981;Dalvit-McPhillips, 1983;Manocha et al, 1986;Pliner & Fleming, 1983;Tarasuk & Beaton, 1991). However, in both non-human primates (Gilbert & Gillman, 1956;Kemnitz et al, 1984;Rosenblatt et al, 1980) and humans (Johnson et al, 1994), food intake has been shown to peak during the mid-luteal phase of the menstrual cycle when progesterone levels are highest, and start declining as progesterone levels drop during the late luteal phase. Therefore, the increases in food intake observed between the premenstrual and postmenstrual phases in many studies could be accounted for by the increased food intake during the mid-luteal phase.…”
Section: Food Intake Effects Of Menstrual Cycle Phasementioning
confidence: 90%
“…18 In the majority of women the menstrual cycle averages 28 days, where the day of onset of menstruation is generally referred to as day 1. 19 The cycle can be divided into four phases: menstruation or early follicular phase (days 1-4), late follicular phase (days 5-11), periovulation (days 12-15) and the luteal phase (days [16][17][18][19][20][21][22][23][24][25][26][27][28]. 19 The culmination of the follicular phase occurs when ovulation takes place around day 14 or 15.…”
Section: Hormonal Changes During the Menstrual Cyclementioning
confidence: 99%
“…[24][25][26][27][28][29][30] Consequently, it has been hypothesized that estrogens reduce appetite and EI and are thus reciprocal to a possible appetite-stimulating effect of progesterone in animals. In humans, a review has summarized EI in relation to menstrual cycle phases in 30 studies, which included a total of 37 groups of women.…”
Section: Energy Intakementioning
confidence: 99%